Molecular dynamics simulations of copper binding to amyloid-β Glu22 mutants. Issue 1 (January 2020) - Mutter, Shaun T.; Turner, Matthew; Deeth, Robert J.; Platts, James A.
Abstract: We report microsecond timescale ligand field molecular dynamics simulations of the copper complexes of three known mutants of the amyloid-β peptide, E22G, E22Q and E22K, alongside the naturally occurring sequence. We find that all three mutants lead to formation of less compact structures than the wild-type: E22Q is the most similar to the native peptide, while E22G and especially E22K are markedly different in size, shape and stability. Turn and coil structures dominate all structures studied but subtle differences in helical and β-sheet distribution are noted, especially in the C-terminal region. The origin of these changes is traced to disruption of key salt bridges: in particular, the Asp23-Lys28 bridge that is prevalent in the wild-type is absent in E22G and E22K, while Lys22 in the latter mutant forms a strong association with Asp23. We surmise that the drastically different pattern of salt bridges in the mutants lead to adoption of a different structural ensemble of the peptide backbone, and speculate that this might affect the ability of the mutant peptides to aggregate in the same manner as known for the wild-type. Abstract : Theoretical chemistry, Molecular dynamics, Copper, Salt bridges, Amyloid peptide